1990
DOI: 10.1002/hlca.19900730105
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Plectranthonen, diterpenoiden Phenanthren‐1,4‐chinonen

Abstract: Synthesis of Plectranthons, Diterpenoid Phenanthrene-1,4-dionesThe following phenanthrene-l,4-diones have been synthesized by using the photocyclization of the corresponding highly substituted stilbenes as the key step : 3-hydroxy-5,7,8-trimethyl-2-(prop-2-enyl)phenanthrene-1,4-dione (l), (RS)-, (R )-, and (S)-2-[3-hydroxy-5,7,8-trimethyl-1,4-dioxophenanthren-2-y1]-1 -methylethyl acetate (2, 31, and 32, resp.), 3-hydroxy-7,8-dimethyl-2-(prop-2-enyl)phenanthrene-1,4-dione (3), 3-hydroxy-7,8,10-trimethyl-2-(prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
1
6
0
2
Order By: Relevance
“…Im vorliegenden Fall entstanden die beiden Regioisomere 22 und 23 in einem Regioisomerenverhältnis r.r. Weitere einfache Phenanthren-Naturstoffe, die durch eine [6p]-Cyclisierung zugänglich wurden, sind die Plectranthone, [29] die Aristolochische Säure, [30] (AE )-Tylophorin, [31] die Phenanthrene TaIV und TaVIII [32] und das diterpenoide Chinon (AE )-Danshexinkun A. [33] Selbst am Ende einer Synthese von komplexen Phenanthrenen kann die [6p]-Cyclisierung effektiv als Schlüsselreaktion eingesetzt werden.…”
Section: Aufsätzeunclassified
“…Im vorliegenden Fall entstanden die beiden Regioisomere 22 und 23 in einem Regioisomerenverhältnis r.r. Weitere einfache Phenanthren-Naturstoffe, die durch eine [6p]-Cyclisierung zugänglich wurden, sind die Plectranthone, [29] die Aristolochische Säure, [30] (AE )-Tylophorin, [31] die Phenanthrene TaIV und TaVIII [32] und das diterpenoide Chinon (AE )-Danshexinkun A. [33] Selbst am Ende einer Synthese von komplexen Phenanthrenen kann die [6p]-Cyclisierung effektiv als Schlüsselreaktion eingesetzt werden.…”
Section: Aufsätzeunclassified
“…(±)-Modephene (163) was synthesized by elaboration of the tetracyclic ketone 162, which itself was accessible by ODPM rearrangement of 161 (50%) (eq 26). 62 The synthesis of 2,8-didehydronoradamantan-9-one (167) was performed starting from brend-4-en-2-one (164) The enantiospecific ODPM transformation of bridged 0,7-unsaturated ketones has paved the way to a ready access to enantiomeric target compounds.480 C. Azadl-r-methane Rearrangements Horspool and colleagues have studied in great detail the effect of substituents with respect to the formation of cyclopropylimines from a,/3-unsaturated imines or azadi-ir-methane (ADPM) systems.54 It was found that electron-withdrawing groups located on the nitrogen atom have a beneficial influence on the ADPM rearrangement. Thus, the acetoxy-substituted imine 168 afforded compound 169 in the presence of suitable sensitizers.…”
Section: Dl-ir -Methane-type Rearrangementsmentioning
confidence: 99%
“…Other simple phenanthrene natural products that were made by means of a [6π] cyclization include the plectranthones,29 aristolochic acid,30 (±)‐tylophorine,31 the phenanthrenes TaIV and TaVIII,32 and the diterpenoid quinone (±)‐danshexinkun A 33. The [6π] cyclization can even be used effectively in the final stages of the synthesis of complex phenanthrenes.…”
Section: Photocyclizationsmentioning
confidence: 99%